2013
DOI: 10.1007/s10103-013-1384-4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic effects of LLLT on bone repair around PLLA–PGA screws in the rabbit tibia

Abstract: To evaluate the systemic effects of low level laser therapy (LLLT) on the early stages of bone repair after implantation of poly-L-lactic/polyglycolic acid (PLLA-PGA) screws 24 rabbits were randomly allocated to one of two groups, experiment or control. Each animal underwent implantation of one 5 × 1.5 mm PLLA-PGA screw in each tibia (right and left). The experiment group received infrared laser irradiation (830 nm, 4 J, 100 mW, 10.1 s) over the right paw immediately after implantation and every 48 h thereafte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…12 We assumed that LLLT applied to the lower face could lead to indirect exposure of the thyroid gland, as 830 nm wavelength lasers can reach deeper planes and exert both local and systemic effects. 5,6,[28][29][30]36,38 The rabbit model was chosen because of the previously reported ease of handling, surgical preparation, and postoperative follow-up. 8,28,34,38 Moreover, the size of these animals enabled the use of conventional implants available for clinical use in humans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12 We assumed that LLLT applied to the lower face could lead to indirect exposure of the thyroid gland, as 830 nm wavelength lasers can reach deeper planes and exert both local and systemic effects. 5,6,[28][29][30]36,38 The rabbit model was chosen because of the previously reported ease of handling, surgical preparation, and postoperative follow-up. 8,28,34,38 Moreover, the size of these animals enabled the use of conventional implants available for clinical use in humans.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,[28][29][30]36,38 The rabbit model was chosen because of the previously reported ease of handling, surgical preparation, and postoperative follow-up. 8,28,34,38 Moreover, the size of these animals enabled the use of conventional implants available for clinical use in humans. As for implant placement in fresh tooth extraction sockets, we chose this method of implant placement, rather than the tibia (which is the most common site reported in the literature), in order to provide the closest possible simulation of a clinical situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in this study, it could be observed in the group that was irradiated. A systemic effect of photobiomodulation has been observed when applied to bone tissue, according to the work of Coelho et al 20 Another important point to be considered is the dosimetry delivered to the tissue, given that the irradiation parameters were taken from a study that used cold burn instead of scalding. 13 In burns caused by scalding there is dissipation of the thermal energy through the tissue and the amount of hyalinized collagen is higher in comparison to cold burns.…”
Section: Discussionmentioning
confidence: 99%